2006
DOI: 10.1002/pi.1992
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase olefin polymerization over supported metallocene/MAO catalysts: influence of support on activity and polydispersity

Abstract: Three catalysts obtained by supporting bis(n‐butylcyclopentadienyl)zirconium dichloride/methylaluminoxane on: (1) porous crosslinked poly(2‐hydroxyethylmethacrylate‐co‐styrene‐co‐divinylbenzene) particles (CAT1); (2) swellable crosslinked poly(styrene‐co‐divinylbenzene) particles (CAT2); and (3) by evaporating the catalyst precursors solution to dry powder, CAT3 were used in gas‐phase polymerization of ethylene, and ethylene/1‐hexene in a 2 L semi‐batch reactor at 80 °C and 1.4 MPa. The average polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…In their study of gas phase ethylene copolymerizations, also using supported Cp 2 ZrCl 2 /MAO catalysts, Hammawa and Wanke again found that the comonomer effect was more pronounced for shorter alkenes than for longer ones. However, they also demonstrated that the friability of the support was related to the importance of the comonomer effect, with more compact, less friable particles having a much higher alkene response.…”
Section: Introductionmentioning
confidence: 97%
“…In their study of gas phase ethylene copolymerizations, also using supported Cp 2 ZrCl 2 /MAO catalysts, Hammawa and Wanke again found that the comonomer effect was more pronounced for shorter alkenes than for longer ones. However, they also demonstrated that the friability of the support was related to the importance of the comonomer effect, with more compact, less friable particles having a much higher alkene response.…”
Section: Introductionmentioning
confidence: 97%
“…However, compositional heterogeneity in the resulting copolymer may still occur, even in the case of a single-center catalyst. [13][14][15][16] Fink et al 14 ascribed the compositional distribution of ethylene/1-hexene copolymers prepared with a SiO 2 /methylaluminoxane (MAO)/zirconocene system to the formation, during the initial stages of polymerization, of a copolymer envelope around the catalyst particle. Easier diffusion of the smaller monomer, ethylene, with respect to 1-hexene was proposed to lead to a polymer particle comprising an ethylene-rich center surrounded by an outer layer of the copolymer, thus giving a broad overall chemical composition distribution (CCD).…”
Section: Introductionmentioning
confidence: 99%
“…The same phenomenon was also reported in other researches where copolymerizable monomers took part in polymerization. 49,50 In contrast, the M w of PE in PE/12MMTs composite (12PE1) is close to that of the neat PE. For P-PE5, homopolymerized PE and copolymerized PE were separated by extraction using decalin as solvent in a Soxhlet extractor for 48 h, and then the MMTs in the residue were removed by reacting with hydrogen fluoride (HF) before examination.…”
Section: Resultsmentioning
confidence: 69%